Peran Pelepasan Moral dalam Hubungan antara Kepemimpinan Etis dan Pengambilan Keputusan Tidak Etis pada Akuntan di Indonesia - Lilianawati Lilianawati; Lidwina Andrea; Tan Ming Kuang (Owner : Riset dan Jurnal Akuntansi, 2026)
This study aims to analyze the role of individual moral mechanisms in explaining the relationship between ethical leadership and unethical decision tendencies  in professional accountants. This study examines the influence of moral detachment on unethical decisions and the role of such construct mediation in the relationship between ethical leadership and unethical decisions. The research uses a quantitative approach with a causal design. Data was collected through a questionnaire survey of 281 professional accountants in Indonesia who were selected using purposive sampling techniques. Data analysis was carried out using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of the study show that moral detachment has a positive and significant effect on unethical decisions. Ethical leadership has a negative and significant effect on moral liberation. Moral detachment has been shown to mediate the relationship between ethical leadership and unethical decisions. The direct influence of ethical leadership on unethical decisions is insignificant. These findings confirm that moral mechanisms are the main pathway in explaining accountants' unethical behavior. This study expands on Social Cognitive Theory by demonstrating a full mediation mechanism through moral detachment in linking ethical leadership and unethical decision-making. These findings confirm that internal moral mechanisms play a central role in explaining unethical decisions in the accounting profession. Ethical leadership functions as a shaper of self-regulation and an individual's moral orientation, not as a direct control of behavior. The implications of the study emphasize the importance of strengthening ethical leadership that focuses on preventing moral rationalization and forming ethical awareness in the education, training, and governance of the accounting profession in Indonesia.